2022
DOI: 10.21323/2414-438x-2022-7-3-156-163
|View full text |Cite
|
Sign up to set email alerts
|

Postslaughter state of muscle tissue of pigs depending on the duration of pre-slaughter fasting

Abstract: Changes in the muscle tissue microstructure lead to changes in meat quality. One of the causes of the myopathy development is animal stress. Pigs experience the strongest stress during pre-slaughter holding. The study of the postmortem meat structure depending on fasting time is a topical task. The objects of the research were samples of m. L. dorsi obtained after slaughter from pigs that differed in fasting time: 4 (group 1), 8 (group 2), 10 (group 3), 16 (group 4) and 18 (group 5) hours (N = 20, n = 4). Inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
(42 reference statements)
0
0
0
Order By: Relevance
“…According to Bhat (2018), a high proteolytic enzyme activity, low collagen content, and long sarcomere length are required for high tenderness. In previous studies comparing the collagen content of the semimembranosus muscle in pork and beef, the collagen content in pork was reported to be 4.13 and 5.30 mg/g, while the collagen content in beef was reported to be 6.85 mg/g (Seong et al, 2009;Semenova et al, 2023;Moon et al, 2006). Additionally, in a study comparing the length of sarcomeres, the reported sarcomere lengths of pork and beef were 2.50 μm and 1.89 μm, respectively (Moon et al, 2006).…”
Section: Shear Forcementioning
confidence: 97%
See 1 more Smart Citation
“…According to Bhat (2018), a high proteolytic enzyme activity, low collagen content, and long sarcomere length are required for high tenderness. In previous studies comparing the collagen content of the semimembranosus muscle in pork and beef, the collagen content in pork was reported to be 4.13 and 5.30 mg/g, while the collagen content in beef was reported to be 6.85 mg/g (Seong et al, 2009;Semenova et al, 2023;Moon et al, 2006). Additionally, in a study comparing the length of sarcomeres, the reported sarcomere lengths of pork and beef were 2.50 μm and 1.89 μm, respectively (Moon et al, 2006).…”
Section: Shear Forcementioning
confidence: 97%
“…These differences might be attributed to differences in the fiber compositions of the pork and beef semitendinosus muscles. Considering the muscle fiber composition of the semitendinosus muscle, red and white muscle fibers constitute 10-20% and 64-80% of pork, respectively (Semenova et al, 2023), whereas beef contains 10-30% and 34-58%, respectively (Totland et al, 1988). White muscle fibers are known to have a lower water-holding capacity than red muscle fibers because of their strong glycolytic activity, resulting in the exudation of more water (Kim et al, 2013;Lyu et al, 2024).…”
Section: Electrical Conductivitymentioning
confidence: 99%
“…In the Russian Federation, fast growing hybrid animals from three-breed crossing (LWxDxL) are mainly used for growing pigs for slaughter [7]. Earlier, we studied manifestation of myopathic changes, which are typical of PSE meat and emerge under an effect of lifetime and slaughter factors, in the microstructure of m. longissimus dorsi taken from slaughtered hybrid animals [8,9]. This muscle is the most frequently chosen object of investigations and its characteristics are studied quite well.…”
Section: Introductionmentioning
confidence: 99%